Analisis Bahan Ajar Berwawasan Agraris untuk Pembelajaran IPA di Sekolah Dasar - M. Fadlillah; Bohri Rahman2; Nurul Istiq’Faroh; Ayik Fena Emilda; Debby Rahmawati (Elementary Teacher Education Program, Majalengka University, 2023)
Indonesia as an agricultural country must continue to be introduced and instilled in students in elementary schools. One of them is by incorporating agrarian-oriented materials in learning activities. The purpose of this study was to determine the model of teaching materials with an agrarian perspective for learning in elementary schools. The literature study method was used in data collection, namely by analyzing articles and various literature relevant to the research. The results showed that the teaching materials with an agrarian perspective included agricultural materials, in the form of getting to know agricultural plants, farming activities, and processing of agricultural products. The forms of teaching materials with an agrarian perspective are printed, non-printed, and interactive teaching materials. It is hoped that this teaching material with an agrarian perspective can support science learning in elementary schools, especially in introducing agriculture and instilling an attitude of caring for the environment.